Ontogenesis of Gonadotropin-Releasing Hormone Neurons: A Model for Hypothalamic Neuroendocrine Cell Development - Stevenson, Erica L.; Corella, Kristina M.; Chung, Wilson C. (Frontiers in Endocrinology, 2013)
The vertebrate hypothalamo-pituitary-gonadal (HPG) axis is the anatomical framework responsible for reproductive competence and species propagation. Essential to the coordinated actions of this three-tiered biological system is the fact that the regulatory inputs ultimately converge on the gonadotropin-releasing hormone (GnRH) neuronal system, which in rodents primarily resides in the preoptic/hypothalamic region. In this short review we will focus on: 1) the general embryonic temporal and spatial development of the rodent GnRH neuronal system, 2) the origin(s) of GnRH neurons, and 3) which transcription - and growth factors have been found to be critical for GnRH neuronal ontogenesis and cellular fate-specification. Moreover, we ask the question whether the molecular and cellular mechanisms involved in GnRH neuronal development may also be play a role in the development of other hypophyseal secreting neuroendocrine cells in the hypothalamus.